Resolução de problemas e educação matemática crítica: uma proposta para o ensino de probabilidade. - Fernandes, Flávio Miguel Dos Santos (2018)
The present study is a proposal to the teaching of probability to high school students. A description of the historical and conceptual construction, definitions and theorems about probability as an explanation of classic and frequentist approaches and conditional and geometric probability are presented. . The necessity of an efficient teaching approach was the motivation for the selection of this topic, as well as the official documents. For this construction, concepts and ideas in the teaching of mathematics were used as a theoretical basis for the activity comprehension and methodological strategies, listed next: teaching through problem solving, being Onuchic (1999) as the main reference, with historical characteristics and orientations of teaching of mathematics and critic mathematical education defined by Skovsmose (2008), with important principles and a critic view of role of mathematics on society. With that, a teaching proposal with seven sequential activities is presented. The activities are in accordance with what it was studied and with the theoretical analysis of what is expected on its development. The proposal is not implemented yet, but we expect that it will be implemented, and analyze it in the future.